Polymorphism in Exon 2 of CD1 Genes in Southwest of Iran - Hossein Golmoghaddam; Nargess Arandi; Abbas Ghaderi; Mehrnoosh Doroudchi (Tehran University of Medical Sciences, 2013)
Background: The CD1 family is less variable transmembrane antigen presenting molecules related to the MHC molecules. CD1a and CD1e genes are the most polymorphic ones associated with autoimmune diseases. The aim was to better clarify the map of CD1 genes in Southwest Iranian normal population for implications in vaccine design.Methods: In this study we investigated the polymorphism of CD1a, CD1d and CD1e in 311 healthy individuals from Fars Province in Southwest of Iran by PCR-SSP method.Results: Six of individuals had homozygote CD1a 01/01 genotype and 248 had homozygote CD1a 02/02 genotype. CD1d was found to be monomorphic with all tested individuals showing CD1d 01/01 genotype. Hundred and eleven individuals had homozygote CD1e 01/01 genotype and 48 had homozygote CD1e 02/02 genotype. The frequencies of CD1a 01 and CD1a 02 alleles were 11% and 89% while the frequencies of CD1e 01 and CD1e 02 alleles were 60.1% and 39.9%, respectively. Consistent with previous reports on other genes, a high degree of similarity in CD1a and CD1e allelic distribution was observed between Southwest Iranians and other Indo-European populations. However, the allelic frequency of the CD1a and CD1e alleles showed a significant difference from those of Chinese Han and She populations.Conclusion: These data are notable in the light of relatively recent genetic admixture along the Silk Road. Considering the significance of CD1 alleles in some autoimmune and infectious diseases and with the admixed nature of Iranian population, mapping the distribution of CD1e alleles in different regions of Iran can be useful in future designing of preventive and therapeutic vaccines.